Corporate governance models : a critical assessment - Mastrodascio, Marco (New York, NY : Routledge, 2022)
"The activities carried out in a business organization stem from the contribution of subjects who cooperate in the expectation of obtaining adequate rewards. The ability of organizations to reach a specific level of performance is influenced by the ownership structure, while the management is directed and controlled through a set of rules and incentives. This set regulates the distribution of rights and responsibilities among the board, company management and stakeholders, and it defines the corporate governance model adopted by the organization. The collapse of global organizations across the world have undoubtedly revealed the inherent flaws in the contemporary corporate governance practices. As a result of these international scandals, a great deal of multidisciplinary research has been growing restlessly to define the specificities of each corporate governance model, however, lacking a specific investigation into the presumed existence of the most suitable one. By favouring the synthesis and the inductive procedure, this book analyses the potential existence of the most appropriate corporate governance model based on comparative international analysis of cultural, social and economic factors influencing the organization's choice regarding the corporate governance model to be adopted. This volume will be of interest to researchers, academics, professionals, and students in the fields of corporate governance, international business, and law"--
OCLC-licensed vendor bibliographic record.
Keywords: Corporate governance; BUSINESS & ECONOMICS / Government & Business; BUSINESS & ECONOMICS / International / General